Excitonic Circular Dichroism of Chiral Quantum Rods - Gao, Xiaoqing; Zhang, Xiuwen; Deng, Ke; Han, Bing; Zhao, Luyang; Wu, Minghui; Shi, Lin; Lv, Jiawei; Tang, Zhiyong (Journal of the American Chemical Society, 2017)
As an emerging type of optically active materials, chiral molecules-stabilized semiconductor quantum dots (QDs) have achieved extensive attention. Unfortunately, understanding of the optical characteristics of chiral QDs observed by circular dichroism (CD) spectroscopy remains a great challenge due to their rather weak signals. Herein, we successfully achieve much enhanced CD responses from l- or d-cysteine-stabilized wurtzite CdSe quantum rods (QRs) thanks to their unique optical anisotropy. Furthermore, the optical activity of CdSe QRs is explored to be improved and subsequently become stable with the geometrical aspect ratio (AR) increasing, and such change matches well with alternation of the polarization factor of CdSe QRs. A non-degenerate coupled-oscillator (NDCO) model is established to elucidate the optical activity of chiral QRs, and the positive and negative natures of the CD peaks appearing at the first exciton band are clearly assigned to different transition polarization along 4p z,Se → 5sCd and 4p(x,y),Se → 5sCd, respectively. This work opens the door toward comprehension and design of optically active semiconductor nanomaterials.